Upkeeping a religious foundation from time to time; A case study of "Dharma i Salingsingan" (ninth–tenth century CE) - Dewanti, Tyassanti Kusumo; Bastiawan, Eko; Permata, Kezia; Prihatmoko, Hedwi (Wacana, Journal of the Humanities of Indonesia, 2025)
The toponym Salingsingan is observed in several inscriptions spanning the period 791-836 Śaka (869-914 CE), through the reigns of King Lokapāla until King Daksa. Its occurrences are attributed to an area where a religious foundation was established. From these occurrences, we see several interesting topics to explore regarding the sīma institution, religious foundations (dharma), and the toponymy of early Central Java. Our aim is to demonstrate the management of the dharma of Salingsingan and to determine its present-day location by combining epigraphical records and archaeological remains. The research will first try to lay a foundation of what is meant by the terms sīma and dharma in a general context. Second, it looks at the relevant inscriptions to understand the context of Salingsingan’s occurrences. Third, it will examine how a religious foundation was managed through different patrons. Fourth, it will explore the possible locations of the Salingsingan foundation from the archaeological remains and the provenance of inscriptions. The study reveals different actors and their actions in the foundation at Salingsingan during the ninth and tenth centuries. The study of inscriptions’ provenances and the architectural styles of temples sheds light to the possible location of this foundation: the complex of Candi Asu, Lumbung, and Pendem in kabupaten Magelang. This multidisciplinary methodology of epigraphical and archaeological analysis helps us to ultimately understand the history of the foundation.